2021
DOI: 10.4103/jgmh.jgmh_1_21
|View full text |Cite
|
Sign up to set email alerts
|

Views of the elderly living in old-age homes on psychosocial care needs

Abstract: Background: Older adults are likely to experience psychological and social problems due to decline in physical strength, increased health issues, inadequate financial resources, and family dynamics. In this context, they need psychosocial care services to handle such challenges. Particularly, inmates of old-age homes are more vulnerable to experience such challenges as they are away from the family care. In this background, knowing their views on psychosocial care needs while living in old-age home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous studies also revealed that most of the staff working in OAHs were women. 21,22 Our findings indicate that the program has enhanced the knowledge on ageing, geriatric mental health and brief psychosocial interventions among the staff working in OAHs. Similarly, the self-efficacy of the staff was found to be satisfactory after the training program and even after two months.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies also revealed that most of the staff working in OAHs were women. 21,22 Our findings indicate that the program has enhanced the knowledge on ageing, geriatric mental health and brief psychosocial interventions among the staff working in OAHs. Similarly, the self-efficacy of the staff was found to be satisfactory after the training program and even after two months.…”
Section: Discussionmentioning
confidence: 72%
“…Many of previous studies have shown similar evidence that elderly who live olde-age homes suffer from Socio-psychological health problem such chronic health issues as stress, loneliness, depression, anxiety and other health and social issues as loneliness and lack of familial relationship. Especially staff of old-age homes lack caring for elderly, empathy, insufficient understanding of aging issue and skill to take care of elderly in old-age home led to worsen the lifestyle of elderly [32][33][34][35][36]. Among these elderly persons, widowed/widower and elderly from rural areas have not satisfied much about their life compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Although (Agadi and Baikdey, 2019) just examines limited old age facility, and (Dhungana and Dhungana, 2020) focuses solely on the chronic physical health conditions that only affect the elderly. In (Shivarudraiah et al, 2021) the study's flaws, including its small sample size and selective participant pool, limit the generalizability of its conclusions. In (Shajahan) the recommended therapies are not affordable in middle and poor class elders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shivarudraiah et al, 2021 investigated the psychological care requirements that residents of nursing homes have expressed. Out of the 4 old-age homes that were approached and employed for the study, the researcher used the purposive sampling strategy and had a sample size restriction of 20.…”
mentioning
confidence: 99%